Signals and cues driving intraspecific variation in mixed community biofilms - Chew, Guan Yu (2015)
Biofilms are surface-associated bacteria that can occur as mixed-species communities. Synergistic interactions between members of a Pseudomonas aeruginosa, Pseudomonas protegens and Klebsiella pneumoniae when grown as a mixed-species biofilm have been discovered to reduce intraspecies genetic variation in all three species via both extracellular signals and genetic regulatory pathways. The work done in this project determined that the extracellular signals involved in Pseudomonas protegens genetic variant suppression could not be extracted using standard methods to isolate non-polar compounds. Therefore an extraction protocol targeting polar metabolites was developed using acetonitrile combined with either sodium sulphate or ammonium sulphate. Using this method, it was possible to extract metabolites from K. pneumoniae mono-species biofilm effluent that suppressed variant formation when added back to P. protegens biofilms. This provides a method for subsequent fractionation and identification of active compounds involved in the process. The project also proposed that the recombinase A gene, recA which is involved in DNA repair and stress responses may also play a role in variant suppression. Therefore a gene deletion strategy was devised to knockout recA in P. aeruginosa and P. protegens.